Strategie rozvoje neziskových organizací - Vaculík, Josef (Univerzita Pardubice, 1999)
Orientation on strategic management problems and strategy comes out from the needs of companies both industrial and public in consequence in environmental quality changes caused by transition to market economy. Every organization inteding to develop successfully within changed environment is forced more than ever to compare and evaluate development tendencies in its environment. Comparison, evaluation and reasonable usage of management objective development tendencies information becomes one of the most important demands placed on actusl managers. Likewise our faculty research - Department of Management and Marketing - wants to contribute to strategic management methodology, to development and application first of all on public sector. Submitted article defines basic problems on strategy and contributes to their solution.
Keywords: Neziskové organizace; Rozvoj; Strategie; Strategické řízení